Factors influencing consumer service experience in private hospitals: a study from Bangladeshi perspective - Ullah, G. M. Shafayet; Islam, Md. Rifayat (© 2011 Interdisciplinary Journal of Contemporary Research in Business (IJCRB), 2016)
This article was published in Interdisciplinary Journal of Contemporary Research in Business (IJCRB) [© 2011 Interdisciplinary Journal of Contemporary Research in Business (IJCRB)] and the definite version is available at : http://journal-archieves8.webs.com/138-147.pdf The article website is at: http://journal-archieves8.webs.com/sep11.pdf